2018
DOI: 10.2147/ott.s162667
|View full text |Cite
|
Sign up to set email alerts
|

RRM1 expression and the clinicopathological characteristics of patients with non-small cell lung cancer treated with gemcitabine

Abstract: BackgroundThe usefulness of ribonucleotide reductase catalytic subunit M1 (RRM1) for predicting the therapeutic effects of gemcitabine-containing chemotherapy in patients with non-small cell lung cancer (NSCLC) remains controversial. RRM1-positive patients show unique clinicopathological features.MethodsHere, we performed a meta-analysis to systematically evaluate the relationship between RRM1 expression and the clinicopathological characteristics of NSCLC patients treated with gemcitabine-containing regimens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…RRM1 could regulate metabolization and activity of mitotane 23 . Previous research has demonstrated that higher RRM1 expression is discovered to associated with shorter overall survival in non‐small cell lung cancer (NSCLC), 24 non‐muscle‐invasive bladder cancer (NMIBC) 25 and multiple myeloma patients 26 . UCK2 could convert uridine and cytidine to uridine monophosphate (UMP) and cytidine monophosphate (CMP), promoting metastasis of HCC cells via the STAT3/MMP2/MMP9 signal axis 27 .…”
Section: Discussionmentioning
confidence: 99%
“…RRM1 could regulate metabolization and activity of mitotane 23 . Previous research has demonstrated that higher RRM1 expression is discovered to associated with shorter overall survival in non‐small cell lung cancer (NSCLC), 24 non‐muscle‐invasive bladder cancer (NMIBC) 25 and multiple myeloma patients 26 . UCK2 could convert uridine and cytidine to uridine monophosphate (UMP) and cytidine monophosphate (CMP), promoting metastasis of HCC cells via the STAT3/MMP2/MMP9 signal axis 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that upregulation of RRM1 has been observed in various cancers, including liver cancer [24,[31][32][33]. The high expression of RRM1 was associated with resistance to DNA-damaging platinum drugs, leading to worse outcomes [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…RRM1 is an important molecular target of gemcitabine because it can control the specificity of a substrate and the activity of an enzyme. Patients with low RRM1 expression had a relatively long survival times after chemotherapy [ 11 , 12 ]. In NMIBC patients treated with intravesical gemcitabine monotherapy, low RRM1 expression patients had longer progression-free survival and lower 1-year/2-year relapse rates, although there is a need to further verify the results [ 13 ].…”
Section: Introductionmentioning
confidence: 99%